From Catalytic Mechanism to Rational Design of Reversible Covalent Inhibitors of Serine and Cysteine Hydrolases. Issue 8 (12th May 2014) - Shokhen, Michael; Hirsch, Michal; Khazanov, Netaly; Ozeri, Rachel; Perlman, Nurit; Traube, Tamar; Vijayakumar, Subramaniam; Albeck, Amnon
Abstract Mechanistic studies of catalysis and the inhibition of serine and cysteine proteases afford new and sometimes surprising insights, challenging conventional dogmas in enzymology. The intrinsic source of the difference in the catalytic mechanisms of serine and cysteine hydrolases, the origin of the stability of the enzymeinhibitor complex in serine proteases, and the structures and mechanisms of catalysis and inhibition in cysteine proteases are not just intellectually interesting; our findings provide a mechanistic basis to understand the trend in the binding affinity of "warheads" of reversible covalent (reaction coordinate analogue, RCA) inhibitors. The theoretically derived covalent descriptors W1 and W2 differentiate serine and cysteine hydrolases and account for the energetic contribution of the new covalent bond in the enzymeinhibitor complex. The W1 and W2 descriptors are at the heart of our enzyme mechanism based method (EMBM); a new computer‐assisted drug design tool for the filtration of inhibitor warheads by activity. EMBM is unique because it accounts for both covalent and noncovalent interactions of RCA inhibitors with their target enzymes.